(untitled) (مجلة الواحات للبحوث والدراسات, 2020)
This Paper Discusses The Subject Of Medical Behaviours In A Anencephalic Newborn. It Attempts To Clarify The Sharia/Jurisprudential Provisions For This Case, Focusing On The Reality Of Having Anencephalic Newborn And Identifying Its Medical Procedures And Symptoms. The Study Aims To Identify The Sharia Provisions For The Medical Procedures Against The Anencephalic Newborn, Such As Abortion Under The Pretext Of Deformities, Not To Revive The Newborn As Being A Medically Hopeless Case, Or The Removal Of Some Of His/Her Organs For The Sake Of Another Person. The Study Revealed A Number Of Findings, The Most Important One Is The Sanctity Of Disposition Of The Anencephalic Newborn In Any Way That Leads To Its Destruction. The Study Recommended The Necessity Of Considering The Sharia Provisions Regarding The Deformed Newborn Babies. Key Words: Anencephalic Newborn, Medical Behaviour, Fetus, Non-Resuscitation, Organs Transplantation.